Factors affecting dry matter intake, daily milk yield and feed conversion ratio in crossbred cows - B. N. SAIKIA, T. BORPUZARI and R. N. GOSWAMI, JAKIR HUSSAIN, R. ROYCHOUDHURY T. K. AMONGE, D. C. MILI, A. AZIZ (Indian Journal of Animal Production and Management, 2020)
The experiment was carried out with 10 Jersey crossbred and 10 Holstein-Friesian crossbred cows duringfour seasons viz. Pre-monsoon, Monsoon, Post-monsoon and Winter in 2016-17. The objectives was tostudy the effect of feeding practice, genetic group and season on the dry matter intake (DMI), daily milkyield (DMY) and feed conversion ratio (FCR) in crossbred cows. The overall mean DMI, DMY and FCR was3.48±0.04 percent, 8.44±0.08 kg and 1.44±0.02, respectively. The effect of feeding practice and geneticgroup was highly significant (P